WORKSHOP PENYUSUNAN MODUL AJAR KURIKULUM MERDEKA BAGI GURU MIM PK TEGALAMPEL, KARANGDOWO, KLATEN - Choirun Nisa; Iqbal Valentino Zulfan; Muhamad Taufik Hidayat; Achmad Januar Arifin; Rofi Anwar Syaputra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
The main objective of this service activity is to organize workshops for MIM PK Tegalampel teachers in developing teaching modules for the Merdeka Curriculum. Explicitly, the results of this community service activity are expected to increase teachers' insights and skills related to developing teaching modules for the Merdeka Curriculum. Additional outputs of this program include the publication of community service articles in community service journals. There are five main stages in this community service activity, from planning to publication. In addition to the agenda, the meeting proposed the formation of a group of workshop presenters consisting of lecturers and students, with students acting as co-presenters. The results of the meeting were then communicated to the partners. The workshop will be organized by a team consisting of 1 lecturer and 3 students, with 13 teachers and 1 principal as participants. The workshop is conducted offline, with face-to-face activities during the briefing. The briefing material is delivered through PowerPoint, followed by the practice of making teaching modules. Evaluation of the success of this activity is based on the tasks done. The task of making Teaching Modules is assessed based on the suitability of its components